CONTENT ANALYSIS OF SPEAKING ACTIVITIES IN ENGLISH TEXTBOOK BASED ON 2013 CURRICULUM FOR THE FIRST GRADE STUDENTS AT SENIOR HIGH SCHOOL - Ali Akbarjono; Pipit Melati; Feny Martina; Syafryadin Syafryadin (University of Kuningan, 2021)
This research is focused on speaking activities in two versions of English Textbooks published by the Government/Kemendikbud and published by Private Publications/Erlangga based on the 2013 Curriculum syllabus, and this research is also to find out which books meet the good category to help student learning activities. This research is very important for the academic world to make it easier for a student and teacher to choose a good textbook to meet their speaking needs. The method used in this research is Content Analysis. The researcher used two analysis matrixes in collecting data. The first analysis matrix will show the suitability of the speaking activities in the two versions of the textbook with the 2013 curriculum syllabus. The second analysis matrix will show the percentage scores of the two versions of the English textbook based on the guidelines evaluation. As for the results of data analysis, the first matrix shows that speaking activities in the two versions of the English textbook are in accordance with the 2013 curriculum syllabus, and the second matrix also shows that the two versions of the English textbook are in the